(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Health Insurance in India became systematic and Simplified Procedure due to regulating authorities like RBI, IRDAI etc. Health insurance is a medical coverage that helps to meet the medical expenses by offering financial assistance. Insurers can be dependent on the word of mouth for the distribution channel as ‘Reference by friends’ seems to be dominant channel for the familiarity of health insurance in the respondents. Media takes the second place for the awareness of health insurance products. 60 percent of respondents still believe health insurance needs to be paid by the individuals rather than government on behalf of insured. With this aspect the present paper made an attempt to discuss health Insurance practice of Policy holders with reference to Krishnagri District of Tamil Nadu.